2007
DOI: 10.1111/j.1440-1789.2007.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress is related to the formation of Antoni B patterns and eosinophilic hyaline droplets in schwannomas

Abstract: Schwannomas, particularly of vestibular origin, often accompany degenerative hypocellular areas known as Antoni B patterns; however, the detailed mechanism is uncertain. Eosinophilic hyaline droplets (EHD), the substantial nature of which are autophagic vacuoles, preferentially appear in acoustic schwannomas and distribute around areas of Antoni B. We investigated their common background using schwannomas with (15 cases) or without (10 cases) EHD, and demonstrated that EHD showed selective immunoreactivity wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In the present case, along with hyalinization of the blood vessels, eosinophilic granular inclusions or hyaline bodies were diffusely observed. Granular inclusions such as those observed in the present case were reported to be frequently observed in intra-cranial schwannomas, especially acoustic schwannomas [19,20], as products of degeneration, and tend to be distributed around the periphery of the Antoni B pattern or area with rich hemosiderin deposition. Pilocytic astrocytoma (PA) should be considered in the differential diagnosis of cerebellar tumors with remarkable degenerative changes.…”
Section: Discussionsupporting
confidence: 67%
“…In the present case, along with hyalinization of the blood vessels, eosinophilic granular inclusions or hyaline bodies were diffusely observed. Granular inclusions such as those observed in the present case were reported to be frequently observed in intra-cranial schwannomas, especially acoustic schwannomas [19,20], as products of degeneration, and tend to be distributed around the periphery of the Antoni B pattern or area with rich hemosiderin deposition. Pilocytic astrocytoma (PA) should be considered in the differential diagnosis of cerebellar tumors with remarkable degenerative changes.…”
Section: Discussionsupporting
confidence: 67%
“…It has been suggested that oxidative stress plays a crucial role in the pathogenesis of schwannoma. 11 Based on the review of literature, in some cases of nasal schwannoma, the patient had diabetes mellitus. 8 In our study, the patient had diabetes for 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…In the present patient, nasal cavity schwannoma originated from the lateral nasal wall, and given that the lateral wall is innervated by anterior ethmoidal nerve, lateral posterior inferior nasal, and lateral posterior superior nasal, it seems that aforementioned schwannoma is associated with above nerve, however, due to the complex pathomechanism of schwannoma, it is not possible to make a definite statement about the origin of this type of schwannoma and the issue is open to As previously mentioned, the pathomechanism of schwannoma is very complex and several factors are involved in its development. It has been suggested that oxidative stress plays a crucial role in the pathogenesis of schwannoma (11). Based on the review of literature, in some cases of nasal schwannoma, the patient had diabetes mellitus (8).…”
Section: Discussionmentioning
confidence: 99%